Batas Usia Perkawinan Menurut UU No. 16 Tahun 2019 dan KUH Perdata Pasal 330 - Nasruddin, Nasruddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This research examines the age limit for marriage according to Law no. 16 of 2019 and the Civil Code Article 330. The writing is motivated by the idea that the age limit for marriage is a must in the formulation of state policies. In fact, in society there are many marriages under the age category of adults which have the potential not to lead to goodness in fostering a family. The formulation of the problem in this study is (1) What are the considerations for the issuance of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage? (2) How is the age limit for marriage determined according to Law Number 16 of 2019 and Article 330 of the Civil Code? The results of this study are that in Islamic law there are no definite provisions relating to the determination of the age limit for marriage, because no specific argument can be found in Al-Qur'an and Sunnah which regulates the issue of the age limit for marriage. So the state is present in determining the age limit for marriage. That there is a change in the times and developments of the times that underlie the renewal of Islamic law and the renewal of legal thought in terms of the age limit for marriage.